Integration effects in border regions - a survey of economic theory and empirical studies - Annekatrin Niebuhr; Silvia Stiller (European Regional Science Association (ERSA), 2002)
Border regions and border effects currently attract a lot of attention in political practice and economic research. Substantial interest in regions located along the frontiers of integrating countries is predominantly inspired by the presumption that their specific geographic position might cause peculiarities in economic adjustments to integration. This survey explores whether economic theory and empirical studies support the assessment that integration effects concentrate in border regions. Economic theory alone allows only very vague conclusions about the spatial effects of integration. Depending on specific circumstances, border regions might benefit, lose or not be affected by integration. Empirical research on border regions - undertaken so far - does not allow to draw clear-cut conclusions as well. At present, there is neither a direct test for integration effects in border regions, nor a comprehensive study on the development of border regions. To sum up, the survey suggests that rigorous theoretical and empirical analysis is needed to foster the understanding of integration effects in border regions.
Keywords: 330